(untitled) (Revista Direitos Humanos e Democracia, 2025)
The theme of this research is the human right to health and the Sustainable Development Goals (SDGs). The general objective is to address the humanitarian challenges for access to healthcare for LGBTQIAPN+ migrants in Brazil. The specific objectives are: 1) Study the importance of achieving SDG nº 3 - Health and well-being to guarantee access to quality health and promote the well-being of migrants; 2) Address the limits and possibilities of access to health for LGBTQIAPN+ migrants in the Brazilian context. Methodologically, the research is implemented using the hypothetical-deductive method, guided by a bibliographic and documentary analysis. The theoretical basis used to design the critical foundation comes from the Theory of Fraternal Law, developed by the Italian jurist Eligio Resta. Given the overlap between the human right to health and the SDGs, the question arises: is it possible to envisage possibilities and challenges to implement the human right to health of LGBTQIAPN+ migrants in Brazil under the theoretical lens of Fraternal Law? It appears that there are countless multidimensional determinants that cross the bodies of migrants and produce a horizon of precariousness and vulnerability of life, a fact that impacts the health and well-being of such subjects. Therefore, it is necessary to incorporate fraternity into public health policies in order to realize the human right to health of LGBTQIAPN+ migrants.